IMPLEMENTASI GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KARYAWAN DI PT BPRS TULEN AMANAH - Ainul Arofah (Jurnal Ekonomi Syariah Darussalam, 2024)
This study aims to find out how good corporate governance is implemented at PT BPRS Tulen Amanah, Masabagik District, and how good corporate governance plays a role in employee performance. The type of research used is descriptive qualitative research, with data collection techniques used, namely observation, documentation, and interviews. The data obtained is then analyzed using an inductive method that starts with a mindset then draws conclusions from specific data and then collects it to a more general level. The results of this study indicate that the implementation of the principles of good corporate governance, namely transparency, accountability, responsibility, fairness and independence have been implemented and juxtaposed with sharia principles. The implementation of good corporate governance has a composite title. "good" with a rating of 2 which includes the operational performance of PT. BPRS Tulen Amanah which implements GCG as a whole and in accordance with existing regulations. and the role of implementing good corporate governance on employee performance has been realized and felt in terms of several criteria, namely the quantity of work, quality of work, knowledge, creativity, cooperation, dependability, and initiative by employees and stakeholders at PT BPRS Tulen Amanah. Keywords: Good Corporate Governance , Employee Performance